2021
DOI: 10.3390/s21186320
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Sensing Analytics Applied to Speech in Reverberation Conditions

Abstract: The paper aims to discuss a case study of sensing analytics and technology in acoustics when applied to reverberation conditions. Reverberation is one of the issues that makes speech in indoor spaces challenging to understand. This problem is particularly critical in large spaces with few absorbing or diffusing surfaces. One of the natural remedies to improve speech intelligibility in such conditions may be achieved through speaking slowly. It is possible to use algorithms that reduce the rate of speech (RoS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Thus, this measure can be used as a substitute for STI measure in cases where the classical STI is not applicable. An example of such a situation is the measurement of systems employing nonlinear speech intelligibility enhancement methods based on, e.g., artificially slowing down the speech signal in reverberant conditions [11]. For such a case, the classical STI measure is not applicable, while the bSTI measure is.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, this measure can be used as a substitute for STI measure in cases where the classical STI is not applicable. An example of such a situation is the measurement of systems employing nonlinear speech intelligibility enhancement methods based on, e.g., artificially slowing down the speech signal in reverberant conditions [11]. For such a case, the classical STI measure is not applicable, while the bSTI measure is.…”
Section: Discussionmentioning
confidence: 99%
“…Using an STI-measuring meter, which is often a compact, hand-held device, is a very compelling way of obtaining fast and repeatable measurements associated with speech intelligibility. Moreover, STI or STIPA and other measures have a substantial drawback which disqualifies their usage in the case of, e.g., evaluation of the performance of algorithms designated for improvement of speech intelligibility of demanding conditions that require non-standard methods of acoustic treatment [11]. This concerns especially locations such as multi-story parking lots or train stations, which are strongly affected by environmental conditions influencing the acoustics of such sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. Odya, J. Kotus, A. Kurowski, and B. Kostek in [ 5 ] analyzed rate of speech in reverberant conditions. As a result, the authors indicated the maximum speech rate required to achieve sentence intelligibility for various acoustic spaces, for Polish language.…”
Section: Overview Of the Contributionsmentioning
confidence: 99%
“…In many cases, their operation must be reliable because the future of enterprises in civil applications or people’s lives in military applications may depend on it. In natural acoustic environments, challenges such as reverberation [ 19 ] or background noise [ 20 ] can be encountered, among others. In addition, there are often dynamics associated with the participation of moving sound sources, e.g., drones, planes, or people, i.e., the Doppler phenomenon [ 21 ].…”
Section: Introductionmentioning
confidence: 99%